(untitled) (Development Service Industry Management, 2024)
The specifics of the processes of determining the main elements and methods of assessing the marketing of the financial and economic security of an enterprise have been studied. Approaches to assessing indicators in marketing management of the economic security of enterprises, including determining the effectiveness of marketing activities, have been analyzed. Having carried out the assessment and analysis, the responsible managers of the enterprise determine the deviations of the actually obtained values of the level of marketing of financial and economic security from the planned ones and make the appropriate management decisions. The need for analyzing the marketing expenses of enterprises on which the effectiveness of marketing support of financial and economic security depends has been substantiated. The estimated financial parameters of ensuring the security of the enterprise have been characterized, which allow determining both the financial condition of the enterprise and the level of marketing support. For enterprises that have sufficient financial and economic potential and activate innovative activities, the calculation of the market coverage ratio of an innovative product is relevant, i.e., forecasting the market share on which the innovation will be implemented. It is important to strengthen monitoring and controlling both the basic indicators of the financial and economic activities of these enterprises and indicators of marketing activities. It is relevant to form a subsystem of basic evaluation indicators of marketing management of the economic security of the enterprise, which will include parameters of sales and product activities, parameters of pricing policy, parameters of marketing costs and determination of the level of financial and economic security of the enterprise.